Ethical challenges of interpreter training at the University of Ljubljana - Maček, Amalija (Verba hispanica, 2021)
Modern society is changing and becoming increasingly multilingual and multicultural. There is a growing need for interpreting in different contexts and for languages that were previously rarely required in the Slovene context (e.g., Albanian, Arabic, and Persian). This paper is based on the premise that if higher interpreter education is to be performed ethically, it must respond to these changes within its capacity and educate interpreters for the languages and fields that society actually needs, thus ensuring respect of human rights in medical, asylum or judicial procedures. In the past, interpreter training at the University of Ljubljana was limited to conference interpreting. However, due to changes in practice the Faculty of Arts has responded to the emerging needs and also formed educational modules for interpreters working in court and asylum procedures, state administration and in medical settings. It continues to invest efforts to expand the range of language combinations to include languages of lesser diffusion, and to offer quality interpreter training to the interpreters of Slovenian sign language. In the academic environment, we are also constantly confronted with internal ethical dilemmas related to the assessment, enrolment, and accreditation processes. It is the latter that significantly slow down the response of the Faculty to needs in society. Despite the numerous administrative, financial and human resources challenges, we may conclude that the Faculty of Arts is committed to investing its maximum efforts and responding with a high level of awareness to the changing interpreting profession which has experienced, through the rapidly growing use of online interpreting platforms, the greatest leap since the introduction of simultaneous interpreting. All this can only be achieved in close cooperation with all the related stakeholders: professional associations, long-standing external trainers and state authorities.
Keywords: adapting study programmes; družbene spremembe; ethics; etika; interpreter training; izobraževanje tolmačev; social change; študijski programi